A botanist's guide to parties and poisons : a novel - Khavari, Kate (Khavari, Kate. Saffron Everleigh mystery, 2022)
Saffron Everleigh is in a race against time to free her wrongly accused professor before he goes behind bars forever. Perfect for fans of Deanna Raybourn and Anna Lee Huber, Kate Khavari's debut historical mystery is a fast paced, fearless adventure. London, 1923. Newly minted research assistant Saffron Everleigh attends a dinner party for the University College of London. While she expects to engage in conversations about the university's large expedition to the Amazon, she doesn't expect Mrs. Henry, one of the professors' wives to drop to the floor, poisoned by an unknown toxin. Dr. Maxwell, Saffron's mentor, is the main suspect, having had an explosive argument with Dr. Henry a few days prior. As evidence mounts against Dr. Maxwell and the expedition's departure draws nearer, Saffron realizes if she wants her mentor's name cleared, she'll have to do it herself. Joined by enigmatic Alexander Ashton, a fellow researcher, Saffron uses her knowledge of botany as she explores steamy greenhouses, dark gardens, and deadly poisons. Will she be able to uncover the truth or will her investigation land her on the murderer's list?